TBIO-12. THE SPECTRUM OF MITOCHONDRIAl DNA (mtDNA) MUTATIONS IN PEDIATRIC CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (4th December 2020) - Kaneva, Kristiyana; Triska, Petr; Merkurjev, Daria; Bootwalla, Moiz; Cotter, Jennifer; Ostrow, Dejerianne; O'Halloran, Katrina; Biegel, Jaclyn; Gai, Xiaowu
Abstract: To explore the role of mitochondrial DNA mutations in pediatric CNS tumors, we analyzed 749 tumor-normal paired whole genome sequencing data sets from the Children's Brain Tumor Tissue Consortium (CBTTC). We detected 307 somatic mtDNA mutations in 222 CNS tumors (29.6%). Most frequently observed were missense mutations (38.1%). We also detected 34 loss-of-function mutations. Different pediatric CNS tumor subtypes have distinct mtDNA mutation profiles. For categorical comparisons, we analyzed subtypes with at least 15 samples. The highest number of mtDNA mutations per tumor sample was in meningiomas (0.85), while atypical teratoid rhabdoid tumors (ATRTs) had the lowest number per sample (0.18). High-grade gliomas had a higher number of mtDNA mutations per sample than low-grade gliomas (0.56 vs. 0.31) (p = 0.0011), with almost twice as many missense mtDNA mutations per sample (0.22 vs. 0.13) (p < 0.001), and higher average heteroplasmy levels (11% vs. 9%). The average heteroplasmy was 10.1%, ranging from 15.6% in medulloblastoma to 6.36% in schwannoma suggesting that these are clonal alterations and not artifacts. Intriguingly, the two chordoma patients in the CBTTC database had an identical heteroplasmic m.10971G>A MT-ND4 nonsense mutation. Similarly, our patient with recurrent gliofibroma harbored the same somatic MT-ND4 synonymous variant (m.10700A>G) detected at 53% heteroplasmy in the initial tumor, 79% in the first recurrence, and 97% in the second recurrence. Although the functional consequences of these alterations are not yet understood, our findings suggest that sequencing the mtDNA genome may be used to characterize CNS tumors at diagnosis and monitor disease progression.